Major Apoptotic Mechanisms and Genes Involved in Apoptosis - Kiraz, Yağmur; Adan, Aysun; Adan Gökbulut, Aysun; Kartal Yandım, Melis; Baran, Yusuf; Kiraz, Yağmur; Baran, Yusuf (SAGE Publications, 2016)
As much as the cellular viability is important for the living organisms, the elimination of unnecessary or damaged cells has the opposite necessity for the maintenance of homeostasis in tissues, organs and the whole organism. Apoptosis, a type of cell death mechanism, is controlled by the interactions between several molecules and responsible for the elimination of unwanted cells from the body. Apoptosis can be triggered by intrinsically or extrinsically through death signals from the outside of the cell. Any abnormality in apoptosis process can cause various types of diseases from cancer to auto-immune diseases. Different gene families such as caspases, inhibitor of apoptosis proteins, B cell lymphoma (Bcl)-2 family of genes, tumor necrosis factor (TNF) receptor gene superfamily, or p53 gene are involved and/or collaborate in the process of apoptosis. In this review, we discuss the basic features of apoptosis and have focused on the gene families playing critical roles, activation/inactivation mechanisms, upstream/downstream effectors, and signaling pathways in apoptosis on the basis of cancer studies. In addition, novel apoptotic players such as miRNAs and sphingolipid family members in various kind of cancer are discussed.
Keywords: Caspase; Protein bcl 2; Protein p53; Tumor necrosis factor